PERAN BIMBINGAN DAN KONSELING UNTUK MENINGKATKAN KONSEP DIRI ANAK USIA DINI - Sustikasari, Sustikasari (Generasi Emas, 2018)
This research is motivated by the phenomenon of early childhood problems caused by low self-concept. Self-concept is a person's perspective, including understanding, assessment, and expectations of himself regarding both physical, psychological, and social self. Self-concept can form the cognitive structure of students to do something either take positive actions or take negative actions. Students who have a positive self-concept show good achievement in school, or high-achieving students in schools have high self-ratings and show positive interpersonal relationships. Students are able to determine realistic learning achievement targets and direct academic anxiety with hard and diligent learning, and student activities are always directed at learning, and not dependent on the teacher.